Endothelin-converting enzyme-1 regulates endosomal sorting of calcitonin receptor-like receptor and β-arrestins - Benjamin E. Padilla; Graeme S. Cottrell; Dirk Roosterman; Stella Pikios; Laurent Muller; Martin Steinhoff; Nigel W. Bunnett (2007)
Although cell surface metalloendopeptidases degrade neuropeptides in the extracellular fluid to terminate signaling, the function of peptidases in endosomes is unclear. We report that isoforms of endothelin-converting enzyme-1 (ECE-1a–d) are present in early endosomes, where they degrade neuropeptides and regulate post-endocytic sorting of receptors. Calcitonin gene-related peptide (CGRP) co-internalizes with calcitonin receptor-like receptor (CLR), receptor activity-modifying protein 1 (RAMP1), β-arrestin2, and ECE-1 to early endosomes, where ECE-1 degrades CGRP. CGRP degradation promotes CLR/RAMP1 recycling and β-arrestin2 redistribution to the cytosol. ECE-1 inhibition or knockdown traps CLR/RAMP1 and β-arrestin2 in endosomes and inhibits CLR/RAMP1 recycling and resensitization, whereas ECE-1 overexpression has the opposite effect. ECE-1 does not regulate either the resensitization of receptors for peptides that are not ECE-1 substrates (e.g., angiotensin II), or the recycling of the bradykinin B2 receptor, which transiently interacts with β-arrestins. We propose a mechanism by which endosomal ECE-1 degrades neuropeptides in endosomes to disrupt the peptide/receptor/β-arrestin complex, freeing internalized receptors from β-arrestins and promoting recycling and resensitization.